Formulation Development and Evaluation of Once Daily Fexofenadine Hydrochloride Microsponge Tablets - Gade, Ramani; Nama, Sreekanth; Avula, Prameela Rani (Trends in Sciences, 2022)
The objective of present study was to formulate and develop once daily Fexofenadine Hydrochloride tablets to improve the aqueous solubility by microsponge technology. Fexofenadine Hydrochloride is an antihistamine and belongs to BCS class-III with low permeability and poor bioavailability about 30 - 35 %. The microsponges were prepared by Quashi emulsion solvent diffusion method with Quality by design approach. The study of effect of independent variables Eudragit EPO (500 to 1,000 mg), internal phase volume (DM: ETH) (5 to 10 mL) and RPM (500 to 1,000) on responses were analyzed to optimize the formulation with desirable results by using central composite design and response surface method. Optimized formulation F22 showed percent production yield (99.10 %), percent drug entrapment (99.45 %), particle size (94.12 µm) and percent drug release of prepared tablets at 5, 10, 15 and 30 min were 60.6, 80.75, 87.47 and 92.85 %, respectively. It showed Higuchi mechanism of release kinetics by diffusion. In vivo pharmacokinetics of the prepared tablets was studied in rabbits (IAEC/NRML/2022–2023/09) with and without permeation enhancer to find the rate of absorption. when compared to Marketed product -Allegra 24 (F21) with (t1/2 absorption) 0.192711±0.00278 h and MRT 19.10608±0.257571 h and formulation without poloxamer 407 (F22) (t1/2 absorption) 0.165013±0.024164 h and MRT 19.32228±0.764531 h, maximum absorption was observed for the Formulation F23 with poloxamer 407 (15 %) with (t1/2 absorption) of 0.144662±0.006787 h and Mean residence time (MRT) of 24.10796±1.01232 h. Microsponge technique improved the aqueous solubility of the fexofenadine Hydrochloride and Eudragit EPO extended the mean residence time up to 24 h along with improved permeability in presence of Poloxamer 407 to full fill the needs of BCS class-III drug. HIGHLIGHTS Fexofenadine Hydrochloride has poor aqueous solubility and low passive permeability P-Glycoprotein efflux induced intestinal secretion is the reason for the incomplete absorption (35 %) following oral absorption There is a need to increase bioavailability and maintenance of steady state plasma concentration Microsponge drug delivery systems improvise the solubility of drug due to its porous nature Microsponge drug delivery system can fulfill the requirements by increasing the permeability and modifying the drug release from dosage form GRAPHICAL ABSTRACT